IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TGT UNTUK MENINGKATKAN PRESTASI BELAJAR KIMIA SISWA SMA - Ledoh, Cartika Candra; Agnes Teresa Panjaitan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to improve student learning outcomes in colloidal chemistry material, this study uses cooperative learning type teams Games Tournaments (TGT) this study is a classroom action research consisting of two cycles each cycle has four stages including planning, action, observation and reflection. The data used in this study is qualitative descriptive data. The results of the study showed that cooperative learning using TGT can improve student learning outcomes. This can be seen and obtained from the presentation of the achievement of cycles I and II in the activeness scheme from 39.33% to 58.62%, cognitive or student learning outcomes from 10% to 16.33% and for the Affective value aspect from 25.7% to 30.3%.